High-strength degradable flame-retardant composite material as well as preparation method and application thereof
By using composite flame retardant, modified fibers and modified lignin in PET materials, the problem of poor flame retardant performance of PET materials is solved, and the development of composite materials with high strength, degradability and high flame retardant performance has been achieved.
Patent Information
- Application Number
- CN202510323375.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-19
- Publication Date
- 2025-04-15
AI Technical Summary
The poor flame retardant properties of existing PET materials have limited their application in production and life. Improving flame retardant properties usually requires sacrificing their mechanical properties, increasing costs, and reducing market competitiveness.
Compound flame retardants, including CEPPA, BCPPO and hydrotalcite, are used to improve the flame retardant and mechanical properties of the material by modifying fibers and modified lignin. The modified fiber is modified by a silicon-based flame retardant, and the modified lignin is modified by a coupling agent and phytic acid to improve its compatibility with PET and flame retardant properties.
The development of high-strength degradable flame retardant composite materials has been achieved. The tensile strength of the material is 150~165MPa, the impact strength is 12~13KJ/m2, and the limit oxygen index is 35~36.5%, while maintaining good mechanical properties and degradation properties.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of degradable flame-retardant materials, and specifically relates to a high-strength degradable flame-retardant composite material and a preparation method and application thereof. Background Art
[0002] Polyethylene terephthalate, with the chemical formula of COC6H4COOCH2CH2O (PET for short), is obtained by ester exchange of dimethyl terephthalate with ethylene glycol or esterification of terephthalic acid with ethylene glycol to synthesize dihydroxyethyl terephthalate, and then polycondensation reaction. PET has excellent physical and mechanical properties in a wide temperature range, and its long-term use temperature can reach 120°C. It has excellent electrical insulation and its electrical properties are still good even at high temperature and high frequency. It also has good creep resistance, fatigue resistance, friction resistance and dimensional stability. It has been widely used in fabrics, packaging materials and engineering plastics. However, PET has poor flame retardancy and is easy to burn when encountering open flames, which seriously limits its application in production and life. Therefore, how to improve the flame retardancy of PET becomes the key to improving its application.
[0003] At present, the main method for improving the flame retardancy of PET in the prior art is to add flame retardants to PET to improve the flame retardancy of PET. Although this method can improve the flame retardancy of the flame retardant, due to the poor compatibility of the flame retardant with PET and the uneven flame retardancy on the market, in order to make its flame retardant effect meet the requirements, it is often necessary to sacrifice its mechanical properties, resulting in a significant decrease in the performance of PET composite materials and an increase in costs, which in turn reduces the market competitiveness of PET composite materials.
[0004] Therefore, how to improve the flame retardant properties of PET materials while ensuring that they have good mechanical properties has become a technical problem that needs to be solved urgently in this field. Summary of the invention
[0005] The purpose of the present invention is to provide a high-strength degradable flame-retardant composite material and its preparation method and application. The high-strength degradable flame-retardant composite material provided by the present invention not only has excellent mechanical properties, but also has good flame retardant properties.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a high-strength degradable flame-retardant composite material, which comprises the following raw materials by weight: PET: 72-85 parts, flame retardant: 0.2-0.5 parts, modified fiber: 1.0-1.5 parts, modified lignin: 12-20 parts, compatibilizer: 5-10 parts, antioxidant: 0.3-1.0 parts and lubricant: 0.5-0.8 parts; The flame retardant is CEPPA, BCPPO and hydrotalcite; the modified fiber is fiber modified by silicon-based flame retardant; and the modified lignin is lignin modified by coupling agent and phytic acid.
[0007] Preferably, the particle size of the hydrotalcite is 5-30 μm.
[0008] Preferably, the mass ratio of CEPPA, BCPPO and hydrotalcite is (3-5): (1-3): (0.8-1).
[0009] Preferably, the silicon-based flame retardant is polysiloxane, silica gel or silicone resin.
[0010] Preferably, the mass ratio of the modified fiber to the silicon-based flame retardant is 1:(0.01-0.2).
[0011] Preferably, the coupling agent is coupling agent KH550 or coupling agent KH560.
[0012] Preferably, the method for preparing the modified lignin comprises the following steps: (1) Mixing lignin and a coupling agent solution and then performing coupling modification to obtain coupling-modified lignin; (2) The coupled modified lignin obtained in step (1) is mixed with a phytic acid solution and then subjected to water bath modification to obtain modified lignin.
[0013] Preferably, the compatibilizer is maleic anhydride grafted polyethylene or maleic anhydride grafted polypropylene; the antioxidant is antioxidant 1076 and / or antioxidant 1010; and the lubricant is zinc stearate and / or calcium stearate.
[0014] The present invention also provides a method for preparing the high-strength degradable flame-retardant composite material described in the above technical solution, which is characterized by comprising: PET, flame retardant, modified fiber, modified lignin, compatibilizer, antioxidant and lubricant are mixed and then melt-extruded to obtain a high-strength biodegradable flame-retardant composite material.
[0015] The present invention also provides the use of the high-strength degradable flame-retardant composite material described in the above technical solution or the high-strength degradable flame-retardant composite material prepared by the preparation method described in the above technical solution in a candle container.
[0016] The present invention adopts a composite flame retardant, which has a better flame retardant effect than a single type of flame retardant. By adopting hydrotalcite as a flame retardant, it not only has the advantages of low cost, easy availability, non-toxicity and non-irritation, but also has good compatibility compared with other flame retardants. At high temperatures, the hydrotalcite can lose interlayer water and dehydrate the hydroxyl groups on the layers and emit them in the form of water vapor, decompose and release water and CO2 gas, absorb a large amount of heat and dilute the concentration of oxygen, thereby reducing the temperature of the combustion surface of the polymer, preventing the further degradation of the polymer, and playing a flame retardant role. The special layered structure of the hydrotalcite also makes it have a large surface area and surface adsorption active center, which can adsorb harmful gases, especially acidic gases, and thus play a dual function of flame retardancy and smoke suppression. By using silicon-based flame retardants to modify the fibers, on the one hand, the flame retardant properties of the modified fibers can be improved, a protective layer can be formed during combustion, and free radicals can be generated to capture active intermediates, thereby achieving a flame retardant effect. On the other hand, the compatibility of the fibers with PET can be improved, thereby improving the mechanical properties of the PET composite material. Using lignin as a raw material is not only low in cost, but also has good degradability, which can improve the degradability of the composite material. By using coupling agents and phytic acid to modify lignin, not only the flame retardant properties of lignin are improved, but also the compatibility between lignin and PET materials can be improved, thereby improving the dispersibility of lignin in PET composite materials, and then using lignin to improve the mechanical properties of the composite material. Experimental results show that the high-strength degradable flame-retardant composite material provided by the present invention has a tensile strength of 150~165MPa and an impact strength of 12~13KJ / m 2 , the limiting oxygen index is 35~36.5%. DETAILED DESCRIPTION
[0017] The present invention provides a high-strength degradable flame-retardant composite material, which comprises the following raw materials by weight: PET: 72-85 parts, flame retardant: 0.2-0.5 parts, modified fiber: 1.0-1.5 parts, modified lignin: 12-20 parts, compatibilizer: 5-10 parts, antioxidant: 0.3-1.0 parts and lubricant: 0.5-0.8 parts; The modified fiber is a fiber modified by a silicon-based flame retardant; and the modified lignin is a lignin modified by a coupling agent and phytic acid.
[0018] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known to those skilled in the art.
[0019] The raw materials for preparing the high-strength biodegradable flame-retardant composite material of the present invention include 72 to 85 parts of PET by weight. In the present invention, the PET is the matrix material of the composite material. As an embodiment of the present invention, the mass fraction of the PET can be 72 parts, 73 parts, 75 parts, 77 parts, 80 parts, 82 parts or 85 parts.
[0020] Based on 72-85 parts by mass of PET, the raw materials for preparing the high-strength biodegradable flame-retardant composite material of the present invention include 0.2-0.5 parts of flame retardant. In the present invention, the flame retardant is CEPPA, BCPPO and hydrotalcite; the particle size of the hydrotalcite is preferably 5-30 μm; the mass ratio of CEPPA, BCPPO and hydrotalcite is preferably (3-5): (1-3): (0.8-1). The present invention adopts a composite flame retardant, which has a better flame retardant effect than a single type of flame retardant. By adopting hydrotalcite as a flame retardant, it not only has the advantages of low cost, easy availability, non-toxicity and non-irritation, but also has good compatibility compared to other flame retardants. At high temperatures, hydrotalcite can lose interlayer water and dehydrate hydroxyl groups on the laminate and dissipate in the form of water vapor, decompose and release water and CO2 gas, absorb a large amount of heat and dilute the concentration of oxygen, thereby reducing the temperature of the polymer combustion surface, preventing further degradation of the polymer, and playing a flame retardant role; the special layered structure of hydrotalcite also makes it have a large surface area and surface adsorption active center, which can adsorb harmful gases, especially acidic gases, and thus play a dual function of flame retardant and smoke suppression. As an embodiment of the present invention, the mass fraction of the flame retardant can be 0.2 parts, 0.3 parts, 0.4 parts or 0.5 parts.
[0021] Based on the mass fraction of PET being 72 to 85 parts, the raw materials for preparing the high-strength degradable flame-retardant composite material of the present invention include 1.0 to 1.5 parts of modified fiber. In the present invention, the modified fiber is a fiber modified by a silicon-based flame retardant, preferably a seaweed fiber modified by a silicon-based flame retardant; the length of the modified fiber is preferably 3 to 12 mm; the diameter of the modified fiber is preferably 9 to 13 μm; the silicon-based flame retardant is preferably polysiloxane, silica gel or silicone resin, more preferably polysiloxane; the mass ratio of the fiber to the silicon-based flame retardant in the modified fiber is preferably 1: (0.01 to 0.2), more preferably 1: (0.02 to 0.15), and further preferably 1: (0.05 to 0.1). In the present invention, the preparation method of the modified fiber preferably includes: mixing the fiber and the silicon-based flame retardant evenly to obtain the modified fiber. The present invention uses a silicon-based flame retardant to modify the fiber, which can improve the flame retardant properties of the modified fiber, form a protective layer during combustion, and generate free radical capture active intermediates, thereby achieving a flame retardant effect. On the other hand, it can improve the compatibility of the fiber with PET, thereby improving the mechanical properties of the PET composite material. As an embodiment of the present invention, the mass fraction of the modified fiber can be 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts or 1.5 parts.
[0022] According to the mass fraction of PET being 72 to 85 parts, the raw materials for preparing the high-strength degradable flame-retardant composite material of the present invention include modified lignin: 12 to 20 parts. In the present invention, the modified lignin is lignin modified by coupling agent and phytic acid; the coupling agent is preferably coupling agent KH550 or coupling agent KH560, more preferably coupling agent KH550. The present invention uses lignin as a raw material, which is not only low in cost, but also has good degradability, and can improve the degradability of the composite material; by using coupling agent and phytic acid to modify lignin, not only the flame retardant properties of lignin are improved, but also the compatibility between lignin and PET materials can be improved, thereby improving the dispersibility of lignin in PET composite materials, and then using lignin to improve the mechanical properties of the composite material. As an embodiment of the present invention, the mass fraction of the modified lignin can be 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts or 20 parts.
[0023] In the present invention, the preparation method of the modified lignin preferably comprises the following steps: (1) Mixing lignin and a coupling agent solution and then performing coupling modification to obtain coupling-modified lignin; (2) The coupled modified lignin obtained in step (1) is mixed with a phytic acid solution and then subjected to water bath modification to obtain modified lignin.
[0024] In the present invention, the lignin and the coupling agent solution are preferably mixed and then subjected to coupling modification to obtain coupling-modified lignin.
[0025] In the present invention, the lignin is preferably lignin powder; the particle size of the lignin powder is preferably 5-30 μm. The present invention uses lignin powder as a raw material, which is conducive to its uniform dispersion in the PET composite material.
[0026] In the present invention, the lignin is preferably pretreated first, and then mixed with a coupling agent solution for coupling modification. In the present invention, the pretreatment is preferably to mix the lignin with an alkali solution with a concentration of 0.01~0.1mol / L and then perform an activation treatment, and then filter, wash and dry in sequence. In the present invention, the alkali solution is preferably a sodium hydroxide solution; the temperature of the activation treatment is preferably 40~70°C, more preferably 50~60°C; the time of the activation treatment is preferably 2~3h. The present invention has no special restrictions on the specific operations of the filtering, washing and drying, which can be determined according to the technical common sense of those skilled in the art, as long as they can be cleaned. The present invention can remove impurities on the surface of lignin through activation treatment on the one hand, and activate the surface of lignin on the other hand, which is beneficial to the subsequent coupling modification.
[0027] In the present invention, the coupling agent solution is preferably an ethanol solution of the coupling agent; the concentration of the coupling agent solution is preferably 2-5 g / mL, more preferably 3-4 g / mL. The present invention has no particular limitation on the amount of the lignin and the coupling agent solution, as long as the lignin can be completely immersed in the coupling agent solution.
[0028] In the present invention, the coupling modification temperature is preferably 50-70°C, more preferably 55-60°C; the coupling modification time is preferably 2-4h, more preferably 3-4h. The present invention can improve the modification efficiency by controlling the coupling modification parameters.
[0029] In the present invention, after the coupling modification is completed, the coupling modified product is preferably filtered, washed and freeze-dried in sequence. The present invention has no particular limitation on the specific operations of the filtering, washing and freeze-drying, as long as the impurities can be removed.
[0030] After obtaining the coupled modified lignin, the present invention preferably mixes the coupled modified lignin with a phytic acid solution and then performs water bath modification to obtain modified lignin.
[0031] In the present invention, the phytic acid solution is preferably an ethanol solution of phytic acid; the concentration of the phytic acid solution is preferably 2-5 g / mL, more preferably 3-4 g / mL. The present invention has no special restrictions on the dosage relationship between the lignin and the phytic acid solution, as long as the coupled modified lignin is completely immersed in the phytic acid solution. The present invention controls the concentration of the phytic acid solution, which is beneficial to the bonding of phytic acid during subsequent modification.
[0032] In the present invention, the water bath modification is preferably 50-80°C, more preferably 60-70°C; the water bath modification time is preferably 12-36h, more preferably 18-24h. The present invention can bond phytic acid and the coupling agent on the surface of lignin through water bath modification, thereby preventing phytic acid from falling off the surface of lignin.
[0033] In the present invention, after the water bath modification is completed, the product of the water bath modification is preferably filtered, washed and freeze-dried in sequence to obtain modified lignin. The present invention has no particular limitation on the specific operations of the filtering, washing and freeze drying, as long as the impurities can be removed.
[0034] According to the mass fraction of PET being 72 to 85 parts, the raw materials for preparing the high-strength degradable flame-retardant composite material of the present invention include 5 to 10 parts of a compatibilizer. In the present invention, the compatibilizer is preferably maleic anhydride grafted polyethylene or maleic anhydride grafted polypropylene. The present invention can further improve the compatibility of each component by adding a compatibilizer, thereby exerting the flame retardant and gain effect of each component and improving the flame retardant properties and mechanical properties of the composite material. As an embodiment of the present invention, the mass fraction of the compatibilizer can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts.
[0035] Based on 72 to 85 parts by mass of PET, the raw materials for preparing the high-strength degradable flame-retardant composite material of the present invention include 0.3 to 1.0 parts of antioxidant. In the present invention, the antioxidant is preferably antioxidant 1076 and / or antioxidant 1010. In the present invention, the antioxidant can improve the thermal stability of the high-strength degradable flame-retardant composite material. As an embodiment of the present invention, the mass fraction of the antioxidant can be 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts or 1.0 parts.
[0036] Based on 72 to 85 parts by mass of PET, the raw materials for preparing the high-strength biodegradable flame-retardant composite material of the present invention include 0.5 to 0.8 parts of lubricant. In the present invention, the lubricant is preferably zinc stearate and / or calcium stearate. By adding a lubricant, the lubricity of the composite material can be improved, thereby facilitating better extrusion during the preparation process. As an embodiment of the present invention, the mass fraction of the lubricant can be 0.5 parts, 0.6 parts, 0.7 parts or 0.8 parts.
[0037] The present invention adopts a composite flame retardant, which has a better flame retardant effect than a single type of flame retardant. By adopting hydrotalcite as a flame retardant, it not only has the advantages of low cost, easy availability, non-toxicity and non-irritation, but also has good compatibility compared with other flame retardants. At high temperatures, the hydrotalcite can lose interlayer water and dehydrate the hydroxyl groups on the layers and emit them in the form of water vapor, decompose and release water and CO2 gas, absorb a large amount of heat and dilute the concentration of oxygen, thereby reducing the temperature of the combustion surface of the polymer, preventing the further degradation of the polymer, and playing a flame retardant role. The special layered structure of the hydrotalcite also makes it have a large surface area and surface adsorption active center, which can adsorb harmful gases, especially acidic gases, and thus play a dual function of flame retardancy and smoke suppression. By using silicon-based flame retardants to modify the fibers, on the one hand, the flame retardant properties of the modified fibers can be improved, a protective layer can be formed during combustion, and free radicals can be generated to capture active intermediates, thereby achieving a flame retardant effect. On the other hand, the compatibility between the fibers and PET can be improved, thereby improving the mechanical properties of the PET composite material. Using lignin as a raw material is not only low-cost, but also has good degradability, which can improve the degradability of the composite material. By using coupling agents and phytic acid to modify lignin, not only the flame retardant properties of lignin are improved, but also the compatibility between lignin and PET materials can be improved, thereby improving the dispersibility of lignin in PET composite materials, and then using lignin to improve the mechanical properties of the composite material.
[0038] The present invention also provides a method for preparing the high-strength degradable flame-retardant composite material described in the above technical solution, comprising: PET, flame retardant, modified fiber, modified lignin, compatibilizer, antioxidant and lubricant are mixed and then melt-extruded to obtain a high-strength biodegradable flame-retardant composite material.
[0039] The present invention has no special limitation on the operation of mixing PET, flame retardant, modified fiber, modified lignin, compatibilizer, antioxidant and lubricant, and the technical scheme for preparing the mixed material well known to those skilled in the art can be adopted.
[0040] The present invention has no particular limitation on the operation of melt extrusion, and any operation well known to those skilled in the art may be used.
[0041] The preparation method provided by the invention has a simple process and can be prepared using existing equipment without the need to introduce new equipment, thereby reducing production costs and being conducive to large-scale industrial promotion.
[0042] The present invention also provides the use of the high-strength degradable flame-retardant composite material described in the above technical solution or the high-strength degradable flame-retardant composite material prepared by the preparation method described in the above technical solution in a candle container.
[0043] The present invention has no special limitation on the operation of applying the high-strength degradable flame-retardant composite material in a candle container, and the application can be carried out in a manner well known to those skilled in the art.
[0044] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] Example 1 A high-strength biodegradable flame-retardant composite material is prepared from the following raw materials by weight: 80 parts of PET, 0.4 parts of flame retardant, 1.5 parts of modified fiber, 15 parts of modified lignin, 5 parts of compatibilizer, 0.5 parts of antioxidant and 0.6 parts of lubricant; The flame retardant is compounded by CEPPA, BCPPO and hydrotalcite in a mass ratio of 5:2:1; the particle size of the hydrotalcite is 5-30 μm; The modified fiber is seaweed fiber modified by a silicon-based flame retardant, the silicon-based flame retardant is polysiloxane, and the seaweed fiber is fiber-grade sodium alginate; the length of the modified fiber is 3-12 mm, and the diameter is 9-13 μm; the mass ratio of the seaweed fiber to the silicon-based flame retardant is 1:0.1, and the preparation method of the modified fiber is: the fiber and the silicon-based flame retardant are evenly mixed to obtain the modified fiber; In the present invention, the preparation method of the modified lignin is: (1) After mixing lignin powder with a particle size of 5-30 μm and 0.1 mol / L sodium hydroxide solution, the mixture was activated at 60°C for 2 h, followed by filtering, washing and drying in sequence, and then added to a 2 g / mL ethanol solution of coupling agent KH550, coupled and modified at 60°C for 3 h, and finally filtered, washed and freeze-dried in sequence to obtain coupled and modified lignin; (2) adding the coupled modified lignin obtained in step (1) to a 4 g / mL phytic acid ethanol solution, modifying it in a water bath at 65° C. for 18 h, and then filtering, washing and freeze-drying to obtain modified lignin; The compatibilizer is maleic anhydride grafted polyethylene, the antioxidant is antioxidant 1010, and the lubricant is calcium stearate; The preparation method of the high-strength degradable flame-retardant composite material is: PET, flame retardant, modified fiber, modified lignin, compatibilizer, antioxidant and lubricant are stirred and mixed in a mixer, and after being evenly mixed, they are added to a twin-screw extruder, and the temperature of the first zone is set to 273°C, the temperature of the second zone is set to 280°C, the temperature of the third zone is set to 284°C, the temperature of the fourth zone is set to 286°C, the temperature of the fifth zone is set to 276°C, the temperature of the sixth zone is set to 275°C, and the temperature of the die is set to 271°C, and then melt extrusion is carried out, and a high-strength biodegradable flame-retardant composite material is obtained after pelletizing.
[0046] Example 2 The amount of the flame retardant used was 0.2 parts, and other conditions were the same as those in Example 1.
[0047] Comparative Example 1 The dosage of the flame retardant is 0, and other conditions are the same as those in Example 1.
[0048] Comparative Example 2 The flame retardant is compounded by CEPPA and BCPPO in a mass ratio of 5:2, and other conditions are the same as those in Example 1.
[0049] The properties of the composite materials prepared in Examples 1-2 and Comparative Examples 1-2 were tested, and the results are shown in Table 1: Table 1 Properties of the composite materials prepared in Examples 1-2 and Comparative Examples 1-2
[0050] Among them, the tensile strength is tested according to standard GB / T 1040-2008; Impact strength is tested according to standard GB / T 1843-2008; The limiting oxygen index is tested according to the standard GB / T 2406-2008 after the specimens are placed at room temperature for 3 months.
[0051] As can be seen from Table 1, by comparing Examples 1 to 2 with Comparative Example 1, it can be seen that with the increase in the amount of the flame retardant in the composite material, the limiting oxygen index of the composite material shows a significant increasing trend, indicating that the present invention can significantly improve the flame retardant properties of the composite material by adding the flame retardant; and by comparing Example 1 with Comparative Example 1, it can be seen that when other conditions remain unchanged, after the hydrotalcite is omitted, the limiting oxygen index of the composite material decreases slightly, indicating that the present invention can further improve the flame retardant properties of the composite material by introducing the hydrotalcite.
[0052] Example 3 The amount of modified fiber used was 1.0 part, and other conditions were the same as those in Example 1.
[0053] Example 4 The amount of modified fiber used was 1.2 parts, and other conditions were the same as in Example 1.
[0054] Comparative Example 3 The amount of modified fiber used was 0, and other conditions were the same as in Example 1.
[0055] Comparative Example 4 The modified fiber was replaced by seaweed fiber, and other conditions were the same as those in Example 1.
[0056] The properties of the composite materials prepared in Examples 1, 3-4 and Comparative Examples 3-4 were tested, and the results obtained are shown in Table 2, wherein the performance test method is the same as the above; Table 2 Properties of the composite materials prepared in Examples 1, 3-4 and Comparative Examples 3-4
[0057] It can be seen from Table 2 that, by comparing Examples 1, 3, 4 and Comparative Example 3, it can be seen that with the increase of the modified fiber content, the tensile strength of the composite material will also increase. When the modified fiber is omitted, the tensile strength is very low. At the same time, the impact strength and limiting oxygen index of the composite material also show similar trends, indicating that the present invention can improve the mechanical properties and flame retardant properties of the composite material by adding modified fibers; by comparing Example 1 and Comparative Example 4, it can be seen that after the modified fiber is replaced by the unmodified fiber, the mechanical properties and flame retardant properties of the composite material have declined significantly. This is because the unmodified fiber has poor compatibility with the composite material, which will reduce the mechanical properties of the composite material to a certain extent. At the same time, the omission of the flame retardant will also reduce the flame retardant properties of the material.
[0058] Example 5 The amount of modified lignin used was 12 parts, and other conditions were the same as those in Example 1.
[0059] Example 6 The amount of modified lignin used was 20 parts, and other conditions were the same as those in Example 1.
[0060] Comparative Example 5 The dosage of modified lignin was 0, and other conditions were the same as those in Example 1.
[0061] Comparative Example 6 The amount of modified lignin used was 5 parts, and other conditions were the same as those in Example 1.
[0062] Comparative Example 7 The amount of modified lignin used was 40 parts, and other conditions were the same as those in Example 1.
[0063] Comparative Example 8 The modified lignin was replaced with ordinary lignin powder, and other conditions were the same as those in Example 1.
[0064] The properties of the composite materials prepared in Examples 1, 5-6 and Comparative Examples 5-8 were tested, and the results are shown in Table 3, wherein the performance test method is the same as the above; Table 3 Properties of the composite materials prepared in Examples 1, 5-6 and Comparative Examples 5-8
[0065] As can be seen from Table 3, by comparing the data of Examples 1, 5-6 and Comparative Examples 5-6, it can be seen that with the increase in the amount of modified lignin in the composite material, the tensile strength, impact strength and flame retardant properties of the composite material all show different changes, among which the tensile strength and impact strength show a trend of first increasing and then decreasing. After analysis, this is due to the excessive amount of modified lignin, which leads to its uneven distribution in the composite material, and the increase in flame retardant properties indicates that the modified lignin provided by the present invention can improve the flame retardant properties of the composite material; by comparing Example 1 and Comparative Example 8, it can be seen that when ordinary lignin powder is used to replace the modified lignin, the mechanical properties and flame retardant properties of the composite material are both reduced. It is speculated that this is because the unmodified lignin powder has poor compatibility with the composite material, so its effect of improving the mechanical properties cannot be fully exerted, and the omission of coupling agent and phytic acid leads to the deterioration of the flame retardant properties of lignin, which in turn affects the flame retardant properties of the composite material.
[0066] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high-strength biodegradable flame-retardant composite material, comprising the following raw materials by weight: PET: 72-85 parts, flame retardant: 0.2-0.5 parts, modified fiber: 1.0-1.5 parts, modified lignin: 12-20 parts, compatibilizer: 5-10 parts, antioxidant: 0.3-1.0 parts and lubricant: 0.5-0.8 parts; The flame retardant is CEPPA, BCPPO and hydrotalcite; the modified fiber is fiber modified by silicon-based flame retardant; and the modified lignin is lignin modified by coupling agent and phytic acid.
2. The high-strength biodegradable flame-retardant composite material according to claim 1, characterized in that: The particle size of the hydrotalcite is 5-30 μm.
3. The high-strength biodegradable flame-retardant composite material according to claim 2, characterized in that: The mass ratio of CEPPA, BCPPO and hydrotalcite is (3-5): (1-3): (0.8-1).
4. The high-strength biodegradable flame-retardant composite material according to claim 1, characterized in that: The silicon-based flame retardant is polysiloxane, silica gel or silicone resin.
5. The high-strength biodegradable flame-retardant composite material according to claim 1, characterized in that: The mass ratio of the modified fiber to the silicon-based flame retardant is 1:(0.01-0.2).
6. The high-strength biodegradable flame-retardant composite material according to claim 1, characterized in that: The coupling agent is coupling agent KH550 or coupling agent KH560.
7. The high-strength biodegradable flame-retardant composite material according to claim 1, characterized in that: The preparation method of the modified lignin comprises the following steps: (1) Mixing lignin and a coupling agent solution and then performing coupling modification to obtain coupling-modified lignin; (2) The coupled modified lignin obtained in step (1) is mixed with a phytic acid solution and then subjected to water bath modification to obtain modified lignin.
8. The high-strength biodegradable flame-retardant composite material according to claim 1, characterized in that: The compatibilizer is maleic anhydride grafted polyethylene or maleic anhydride grafted polypropylene; the antioxidant is antioxidant 1076 and / or antioxidant 1010; and the lubricant is zinc stearate and / or calcium stearate.
9. The method for preparing the high-strength degradable flame-retardant composite material according to any one of claims 1 to 8, characterized in that: include: PET, flame retardant, modified fiber, modified lignin, compatibilizer, antioxidant and lubricant are mixed and then melt-extruded to obtain a high-strength biodegradable flame-retardant composite material.
10. Use of the high-strength degradable flame-retardant composite material according to any one of claims 1 to 8 or the high-strength degradable flame-retardant composite material prepared by the preparation method according to claim 9 in candle containers.
Citation Information
Patent Citations
Material for light flame-retardant heat-shrinkable insulating sleeve and preparation method of material
CN113462065A
Flame-retardant and smoke-suppressing soft polyvinyl chloride composite material having good mechanical performance and preparation method therefor
WO2020233028A1